Fabrication of CuWO4@MIL-101 (Fe) nanocomposite for efficient OER and photodegradation of methylene blue - Mariam Khan; Muhammad Mahboob Ahmed; Muhammad Nadeem Akhtar; Muhammad Sajid; Nagina Naveed Riaz; Muhammad Asif; Muhammad Kashif; Bushra Shabbir; Khalil Ahmad; Muhammad Saeed; Maryam Shafiq; Tayyaba Shabir (Heliyon)
The development of an efficient catalyst to meet the world's increasing energy demand and eliminate organic pollutants in water, is a concern of current researchers. In this article, a highly effective composite has been synthesized using the solvothermal approach, by incorporating CuWO4 nanoparticles into Fe-based MOF, Fe (BDC). The synthesized samples were analyzed further by some characterization techniques such as X-ray diffraction, Fourier transform infrared spectroscope (FTIR) and scanning electron microscopy. The highest catalytic activity for the oxygen evolution reaction was observed in the CuWO4@MIL-101(Fe) composite, which exhibited low overpotential 188 mV to obtained the current density of 10 mA cm−2, and a smaller Tafel slope of 40 mV dec−1. The nanocomposite CuWO4@MIL-101(Fe) material showed enhanced visible light absorption and maximum degradation of methylene blue up to 96.92 %. It has been found that this research promotes the development of an efficient MOF-based catalyst for OER and photocatalytic technology.